Pitfalls of DSGE model approach in monetary union - Zlatica Konôpková (DANUBE: Law, Economics and Social Issues Review, 2019)
This paper investigates the impact of country size on the DSEG model estimation of the monetary union. Following DSGE model for fiscal policy simulations (FiMod) the union is considered to have a two-country structure, the investigated country has weight in union equal to its population share and the second country represents the rest of members. The model is estimated for different country sizes and it is found there are two areas of equilibrium instability which covers 11 of 19 European Monetary Union members. The result is in contrary with Stähler and Thomas (2012) who estimated FiMod for Spain and stated that model can be recalibrated to every member of the monetary union. According to the result the size of country matters and affects the stability of equilibrium. Therefore, special attention is paid to small economies in monetary union. The results and consequences are then discussed with examples from recent history.
Keywords: 330; DSGE; Fiscal Policy; Small Economy; Union